High technology research and applications 2015 - Martyushev, Nikita; Bogdan, Anna (Key engineering materials, 2016)
The Proceedings "High Technology: Research and Applications 2015" covers a wide range of scientific areas and modern trends in science and technology. This book of Proceedings presents selected papers on chemistry, discharge and plasma technologies, nanomaterials, mechanical engineering, optics, IT, etc. The presented scientific works were carried out by academics as well as by industrials. The aim of the Proceedings is to present and discuss the actual state of the studies in the relevant fields and to show the prospects of its development.